A negation query engine for complex query transformations - Iqbal, Rizwan; Azmi Murad, Masrah Azrifah (Universiti Putra Malaysia Press, 2013)
Natural language interfaces to ontologies allow users to query the system using natural language queries. These systems take natural language query as input and transform it to formal query language equivalent to retrieve the desired information from ontologies. The existing natural language interfaces to ontologies offer support for handling negation queries; however, they offer limited support for dealing with them. This paper proposes a negation query handling engine which can handle relatively complex natural language queries than the existing systems. The proposed engine effectively understands the intent of the user query on the basis of a sophisticated algorithm, which is governed by a set of techniques and transformation rules. The proposed engine was evaluated using the Mooney data set and AquaLog dataset, and it manifested encouraging results.